Effects of Self Efficacy and Risk Taking Behavior on Personal Growth Initiative of University Students (Journal of Asian Development Studies, 2018)
This study is undertaken to investigate the combined effect of self efficacy and risk taking behavior on person growth initiative of university students. Data was collected from the students of Mohammad Ali Jinnah University Islamabad (N=273, Male=140, Female=133, Graduate=59, Undergraduate=214). Regression analysis was carried out to know the effects of self efficacy and risk taking behavior on personal growth initiative of university students. Correlation analyses reveal that all variables are positively integrated. The regression analyses indicate that 18% positive variations are explained by self efficacy and risk taking behavior in personal growth initiative. Based on results it is suggested that there should be motivational programs regarding self efficacy and risk taking. This will further leads to enhance the personal growth initiative level of university students.